The Influence of Auditors Gender and CFO Gender to Earnings Quality - Hendi Hendi; M Imam Sarosdak (Budapest International Research and Critics University, 2023)
Influence of Gender Auditor and Gender CFO on Earnings quality. This research was conducted on companies listed on the IDX in 2017-2021. The selected sample results contain 1,388 observational data. The procedure for analyzing the information used is using linear regression analysis. The research results prove that Gender Auditor and Gender CFO have no significant effect on Earnings Quality.